A novel treatment of bromelain and acetylcysteine (BromAc) in patients with peritoneal mucinous tumours: A phase I first in man study. Issue 1 (January 2021) - Valle, S.J.; Akhter, J.; Mekkawy, A.H.; Lodh, S.; Pillai, K.; Badar, S.; Glenn, D.; Power, M.; Liauw, W.; Morris, D.L.
Abstract: Background: Bromelain (Brom) and Acetylcysteine (Ac) have synergistic activity resulting in dissolution of tumour-produced mucin both in vitro and in vivo . The aim of this study was to determine whether treatment of mucinous peritoneal tumour with BromAc can be performed with an acceptable safety profile and to conduct a preliminary assessment of efficacy in a clinical setting. Methods: Under radiological guidance, a drain was inserted into the tumour mass or intraperitoneally. Each patient could have more than one tumour site treated. Brom 20–60 mg and Ac 1·5-2 g was administered in 5% glucose. At 24 h, the patient was assessed for symptoms including treatment-related adverse events (AEs) and the drain was aspirated. The volume of tumour removed was measured. A repeat dose via the drain was given in most patients. All patients that received at least one dose of BromAc were included in the safety and response analysis. Findings: Between March 2018 and July 2019, 20 patients with mucinous tumours were treated with BromAc. Seventeen (85%) of patients had at least one treatment-emergent AE. The most frequent treatment-related AEs were CRP rise (n = 16, 80%), WCC rise (n = 11, 55%), fever (n = 7, 35%, grade I) and pain (n = 6, 30%, grade II/III). Serious treatment-related AEs accounted for 12·5% of all AEs. There were no anaphylactic reactions. There were no deaths due to treatment-related AEs. An objective response to treatment was seen in 73·2% of treated sites. Conclusion: Based on these preliminary results and our preclinical data, injection of BromAc into mucinous tumours had a manageable safety profile. Considerable mucolytic activity was seen by volume of mucin extracted and radiological appearance. These results support further investigation of BromAC for patients with inoperable mucinous tumours and may provide a new and minimally invasive treatment for these patients.